Macroautophagy Proteins Control MHC Class I Levels on Dendritic Cells and Shape Anti-viral CD8+ T Cell Responses - Loi, Monica; Müller, Anne; Steinbach, Karin; Niven, Jennifer; Barreira da Silva, Rosa; Paul, Petra; Ligeon, Laure-Anne; Caruso, Assunta; Albrecht, Randy A.; Becker, Andrea C.; Annaheim, Nicolas; Nowag, Heike; et al. (Cell reports (Cambridge), 2016)
The macroautophagy machinery has been implicated in MHC class II restricted antigen presentation. Here, we report that this machinery assists in the internalization of MHC class I molecules. In the absence of the autophagy factors Atg5 and Atg7, MHC class I surface levels are elevated due to decreased endocytosis and degradation. Internalization of MHC class I molecules occurs less efficiently if AAK1 cannot be recruited via Atg8/LC3B. In the absence of Atg-dependent MHC class I internalization, dendritic cells stimulate CD8+ T cell responses more efficiently in vitro and in vivo. During viral infections, lack of Atg5 results in enhanced influenza- and LCMV-specific CD8+ T cell responses in vivo. Elevated influenza-specific CD8+ T cell responses are associated with better immune control of this infection. Thus, the macroautophagy machinery orchestrates T cell immunity by supporting MHC class II but compromises MHC class I restricted antigen presentation. [Display omitted] •Atg5- and 7-deficient dendritic cells (DCs) have increased surface MHC class I levels•MHC class I internalization is compromised in the absence of Atg5•In the absence of LC3 lipidation, AAK1 gets less efficiently recruited to MHC class I•As a result, anti-viral CD8+ T cell responses are more efficiently stimulated Macroautophagy assists in antigen processing for MHC class II presentation. In contrast to this supportive role for CD4+ T cell stimulation, Loi et al. demonstrate that macroautophagy proteins diminish antigen presentation on MHC class I molecules during anti-viral CD8+ T cell responses by supporting MHC class I internalization in dendritic cells.